SEXUAL AND AGGRESSIVE BEHAVIOR CHANGES IN GOSSYPOL TREATED MALE MICE - Bayaty; Muhannad A. A. A (Basrah Journal of Veterinary Research)
Three groups of male mice, ten mice each, were treated by gossypol acetic acid for (38) day by oral rote successively: group one treated with normal saline served as control, group two treated with 20 mg/Kg. BW. and group three treated with 40 mg/Kg. BW. The treated males were direct faced individually with adult males for aggressive behavior tests, and virgin female diestrus for sexual behavior tests. The results were as follow: the group two and three did not mice show any copulation activities during the 3- hour of observation, group two as well as three mice had less initiative in attacking their opponents and tended to avoid any longer contacts in combating. Afterward group two and three mice got significant body weight changes compared with group one (control). Therefore, the suggested conclusion of the study was gossypol tended to reduce the aggressiveness and sexual activity, but moreover body weight of the male mice was decreased.